Analysis and design of a very low phase-noise Ku-band coupled VCO using a modified cascode architecture in 0.25 μm SiGe:C BiCMOS technology. (May 2018) - Hyvert, Jérémy; Cordeau, David; Paillot, Jean-Marie
Abstract: This paper presents the theoretical principles and the measurement results of a fully integrated Ku-band coupled Voltage Controlled Oscillator (VCO) with very low phase noise, implemented in the QUBiC4X 0.25 μm SiGe:C BiCMOS process of NXP semiconductors. The originality of this design consists in using two coupled VCOs based on an original modified cascode architecture with a customized resonator using a back-to-back varactor configuration. Under 5 V supply voltage and a maximum power dissipation of 231.5 mW, the proposed VCO features a phase noise of −121.4 dBc/Hz at 1 MHz frequency offset. The VCO is tuned from 13.53 GHz to 14.79 GHz with a tuning voltage varying from 1 V to 4.5 V and occupies 0.84 × 1.85 mm 2 .